Analysis of the 'Endoworm' prototype's ability to grip the bowel in in vitro and ex vivo models. (May 2020) - Tobella, Javier; Pons-Beltrán, Vicente; Santonja, Alberto; Sánchez, Carlos; Campillo-Fernández, Alberto J; Vidaurre, Ana
Access to the small bowel by means of an enteroscope is difficult, even using current devices such as single-balloon or double-balloon enteroscopes. Exploration time and patient discomfort are the main drawbacks. The prototype 'Endoworm' analysed in this paper is based on a pneumatic translation system that, gripping the bowel, enables the endoscope to move forward while the bowel slides back over its most proximal part. The grip capacity is related to the pressure inside the balloon, which depends on the insufflate volume of air. Different materials were used as in vitro and ex vivo models: rigid polymethyl methacrylate, flexible silicone, polyester urethane and ex vivo pig small bowel. On measuring the pressure–volume relationship, we found that it depended on the elastic properties of the lumen and that the frictional force depended on the air pressure inside the balloons and the lumen's elastic properties. In the presence of a lubricant, the grip on the simulated intestinal lumens was drastically reduced, as was the influence of the lumen's properties. This paper focuses on the Endoworm's ability to grip the bowel, which is crucial to achieving effective endoscope forward advance and bowel folding.